Children’s bioethics: principles, issues and problems - Lozano Vicente, Agustín (Acta Bioethica, 2017)
From materialistic bioethics developed by the Spanish philosopher Gustavo Bueno and performing an updated review of the existing literature, I present the principles of bioethics child, a classification of issues that arise in this area of knowledge as well as the main problems that arise when incorporating the child as a subject of the bioethical issues. The purpose of this paper is to show how from the status of the child, the children’s Bioethics is irreducible to the matters dealt with by the standard bioethics, which it takes like reference to the adult subject.